Transformation of Risk Communication in the Digital Age: Traditional Media to Digital Media in Maintaining Coastal Community Resilience - Febriana, Kharisma Ayu; Tri Kartono, Pawito Drajat; Rahmanto, Andre Noevi (Jogjakarta Communication Conference (JCC), 2025)
Coastal communities face recurring threats from hydrometeorological disasters that are further exacerbated by climate change and land subsidence. Effective communication is needed to anticipate disaster losses. Currently, disaster communication has been transformed. What disaster transformation looks like is the subject of this research. This research was conducted qualitatively. The research took place in Demak Regency because this location is subject to flooding in Indonesia. Data was collected through in-depth interviews with communities in the district. The purpose of this research is to identify the role of WhatsApp Group Maritim BMKG in disseminating emergency information and its impact on risk perception, preparedness and collective response of coastal communities in disaster mitigation. The research found that disaster communication, which was initially conducted traditionally, has now been transformed into digital. Communication using BMKG's Maritime WhatsApp Group plays an important role in accelerating the dissemination of emergency information, building collective awareness and improving community response in disaster mitigation. WhatsApp shapes and develops the community's perception of disaster risk, which in turn influences preparedness and collective action.